Digital Humanities - Reichert, Ramón (Infotheca - Journal for Digital Humanities; Vol 15 No 2 (2014): Infotheca - Journal for Digital Humanities, 2024)
Digital humanities is a transdisciplinary scientific area that can be seen both as a research subject and as a methodological tool. It connects humanities with information and communication sciences, that is, it connects the pragmatic (user and programing) dimension with the media historical dimension of information technologies and their usage. The term digital humanities hasn’t been established until the emergence of the Internet and realization of the importance of processing of and research over large data sets. Terms that were used before, such as Humanities Computing and Computer Linguistics have been replaced with the concept of humanities in the context of not only digital surroundings, but also digital artefacts as subjects of interest for scientists in the broad field of social sciences. In this paper, we outlined not only the history of Digital Humanities, but also the history of the ideas of digitization, i.e. converting data into another format of presentation, more complex for humans, but easier for machine, computer processing. It is important to point out that in this nexus of disciplines and scientific areas, avid representatives of digital thought are not in conflict with practitioners of digitization. Both of them, in spite of different traditions, follow the general line of the shared ideology of unfaltering confidence in the scientific truth provided by technology. The aim of this text is to reflect upon that truth from the perspective of socio-cultural historical archaeology of science and media.